Psychopathological Risk in Siblings of Subjects with Attention-Deficit/Hyperactivity Disorder: A cross-Sectional Study (2023)
ABSTRACT: Objective: We aim to determine the prevalence of mental disorders in siblings of children with attention deficit hyperactivity disorder (ADHD), and to determine how psychosocial adversity factors relate to this psychopathology, in a low-middle income country (Colombia). Methods: We evaluated subjects with ADHD diagnosed according to the DSM-5 criteria, one of their parents and one of their siblings (ages 8-19). We used the ADHD rating scale and a set of instruments to assess the presence of mental disorders as well as psychosocial adversity. Results: We evaluated 74 trios formed by the index case with ADHD, one sibling and one of the parents. We found that 24.3% of the participating siblings also met the criteria for ADHD and another 24.3% for other psychiatric disorders. The risk of these siblings having ADHD increased further when one of the parents reported a history of ADHD. We also found that 28.3% of the families faced high levels of psychosocial adversity as per their scores in the Rutter Adversity Index. Conclusions: Siblings of subjects with ADHD showed a significant risk for ADHD and other mental disorders. That risk increased if a parent reported a history of ADHD and also when two or more psychosocial adversity factors were present. This study supports the importance of early detection in efforts to decrease the risk for other siblings.